Assessing the mediating effect of leadership styles on favoritism and job performance in family-owned business / Syaimaa Amira Mohamad Yusof and Fadilah Puteh. - Mohamad Yusof, Syaimaa Amira; Puteh, Fadilah (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, 2018)
Family-owned businesses have been criticized for having a lack of leadership effectiveness and yield unfavourable influence on employee’s job performance. Although there are ample studies on favouritism particularly in family-owned businesses, nevertheless very limited studies highlighted on the leadership styles as the significant mediator. This study aims to investigate the mediating effect of leadership styles namely democratic and autocratic styles between favouritism on gender and favouritism on social ties and job performance. Data was collected from 350 respondents via questionnaire and was analysed using correlation, multiple regression and Hayes PROCESS techniques. The findings of this study revealed interesting results of the mediation effect of both democratic and autocratic leadership styles between favouritism and job performance among employees in the family-owned business.